Developmental tumourigenesis: NCAM as a putative marker for the malignant renal stem/progenitor cell population - Pode‐Shakked, Naomi (J Cell Mol Med, 2008)
During development, renal stem cells reside in the nephrogenic blastema. Wilms’ tumour (WT), a common childhood malignancy, is suggested to arise from the nephrogenic blastema that undergoes partial differentiation and as such is an attractive model to study renal stem cells leading to cancer initiation and maintenance. Previously we have made use of blastema‐enriched WT stem‐like xenografts propagated in vivo to define a ‘WT‐stem’ signature set, which includes cell surface markers convenient for cell isolation (frizzled homolog 2 [Drosophila] – FZD2, FZD7, G‐protein coupled receptor 39, activin receptor type 2B, neural cell adhesion molecule – NCAM). We show by fluorescence‐activated cell sorting analysis of sphere‐forming heterogeneous primary WT cultures that most of these markers and other stem cell surface antigens (haematopoietic, CD133, CD34, c‐Kit; mesenchymal, CD105, CD90, CD44; cancer, CD133, MDR1; hESC, CD24 and putative renal, cadherin 11), are expressed in WT cell sub‐populations in varying levels. Of all markers, NCAM, CD133 and FZD7 were constantly detected in low‐to‐moderate portions likely to contain the stem cell fraction. Sorting according to FZD7 resulted in extensive cell death, while sorted NCAM and CD133 cell fractions were subjected to clonogenicity assays and quantitative RT‐PCR analysis, exclusively demonstrating the NCAM(+) fraction as highly clonogenic, overexpressing the WT ‘stemness’ genes and topoisomerase2A (TOP2A), a bad prognostic marker for WT. Moreover, treatment of WT cells with the topoisomerase inhibitors, Etoposide and Irinotecan resulted in down‐regulation of TOP2A along with NCAM and WT1. Thus, we suggest NCAM as a marker for the WT progenitor cell population. These findings provide novel insights into the cellular hierarchy of WT, having possible implications for future therapeutic options.